2022
DOI: 10.3389/fvets.2022.1009182
|View full text |Cite
|
Sign up to set email alerts
|

Negative effects of heat stress on ovarian tissue in female rabbit

Abstract: Numerous studies have highlighted the role of miRNA in the deformation and necrosis of cells of ovarian tissue caused by heat stress (HS), which ultimately affects ovarian function. Although the role of small RNAs has been investigated in alterations in ovarian tissue functioning in response to HS, the expression profile of ovarian miRNA has been explored to a lesser extent. In this study, female rabbits were subject to HS treatment by using electrical heater. The current work demonstrated that HS could signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…In a previous HS experiment with rabbits, our team identified 23 differentially expressed miRNAs, including miR-196a, between tissues under HS and a control condition [5]. This information suggests that miR-196a, identified in the study, could play a role in modulating cellular physiological changes during HS.…”
Section: Introductionmentioning
confidence: 62%
See 2 more Smart Citations
“…In a previous HS experiment with rabbits, our team identified 23 differentially expressed miRNAs, including miR-196a, between tissues under HS and a control condition [5]. This information suggests that miR-196a, identified in the study, could play a role in modulating cellular physiological changes during HS.…”
Section: Introductionmentioning
confidence: 62%
“…These findings suggest that miR-196a may play an important regulatory function in the mammary glands of dairy cows. One of our previous studies suggested that miR-196a may be involved in regulating the alteration of the physiology of the animal organism under HS [5]. We established an HS model using BMECs to investigate whether miR-196a regulates the mammary gland's One of our previous studies suggested that miR-196a may be involved in regulating the alteration of the physiology of the animal organism under HS [5].…”
Section: Heat Stress Downregulates Mir-196a Expression and Suppresses...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies documented that a long exposure to thermal stress resulted in oxidative stress, consequently deteriorating rabbit females' endocrine system and ovarian physiological functions [26,62]. It was noted that exposure to HS reduced the relative weight of the ovary [62,63]. Additionally, exposure to HS resulted in the impairment of ovarian granulosa cells' responsiveness, reducing plasma progesterone concentration, destructing the ovarian cell nucleoli, and weakening the responsiveness of ovarian granulosa cells to follicle-stimulating hormone (FSH) in rabbit does [26].…”
mentioning
confidence: 99%
“…Moreover, HS increased mortality in both adult mothers and offspring and deteriorated offspring growth [26]. Tang et al [63] pointed out that HS had a negative influence on the physiological performance of female rabbits in terms of ovary weight % and plasma contents of interleukin (IL)-2, IL-8, catalase (CAT), and glutathione peroxidase (GSH-Px), and accelerated ovarian apoptosis and unhealthy follicles, as well as altered miRNAs expression in rabbit does. The CAT and GSH-Px play a vital role as antioxidative enzymes in rabbits' earlier phases of folliculogenesis; therefore, exposure to HS suppressed ovarian folliculogenesis, maturation, and ovulation [64].…”
mentioning
confidence: 99%